On the path of writing Reformbill: Origins of Hegel’s Reception of Great Britain: As origens da recepção da Grã-Bretanha por Hegel (Revista Eletrônica Estudos Hegelianos, 2023)
The article focuses on the investigation of the reception of themes around Great Britain in Hegel’s thought. For this, it observes both the assimilation of historical and political aspects of Great Britain and the specifically theoretical dimension expressed notably with regard to political economy. The article argues that this reception had an important moment during Hegel’s stay in Bern, a privileged center for the reception of English ideas, through the incorporation of authors present in the Steigers’ library in Tschugg. In addition, the article makes some observations on how to understand Hegel’s empirical studies in the face of his theoretical elaborations.